How knowledge on land values influences rural-urban development processes - Emília Malcata Rebelo (2013)
This chapter stresses how important knowledge of land and real estate values and their interdependencies, their underlying variables and valuation processes, the relations between rural and urban land, temporal perspectives of land use changes, as well as behaviour of agents involved in development processes are for successful regional and urban planning. It specifically focuses on the importance to control surplus-values generation and assure its fair distribution on behalf of the society in general, thus avoiding land speculation. Within this scope, it is proposed and developed a methodology for the evaluation and computation of surplus-values that is applied, as a case study, to the office market in Oporto city (Portugal), despite it can be easily generalised to other property realities. Furthermore, inferences and conclusions are drawn concerning the implications of this analysis for regional and urban planning, especially at the fiscal level. This methodology is expected to support better planning decisions concerning a balanced rural-urban development, thus fuelling a stronger sustainability of rural areas.